Weighted splicing systems - Turaev, Sherzod; Gan, Yee Siang; Othman, Mohamed; Sarmin, Nor Haniza; Fong, Wan Heng (Springer, 2012)
In this paper we introduce a new variant of splicing systems, called weighted splicing systems, and establish some basic properties of language families generated by this type of splicing systems. We show that a simple extension of splicing systems with weights can increase the computational power of splicing systems with finite components.